(untitled) (Bangladesh Journal of Scientific Research, 2014)
A longitudinal non-linear binary dynamic (NLBD) model which provides a full range for the longitudinal correlation parameter was attempted to analyze longitudinal morbidity data for determining the potential determinants of antenatal care (ANC) seeking behavior of pregnant women during their pregnancies. The regression and dependence parameters were estimated by optimal generalized quasilikelihood (OGQL) estimation approach. The estimate of dependence parameter was found to be significantly large. Age at marriage, economic status, husband’s occupation, distance from health facility and numbers of previous pregnancies were found to have significant impact on the ANC seeking behavior DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20227 Bangladesh J. Sci. Res. 26(1-2): 21-28, December-2013